Integration of Eastern Europe Into the World Trading System - Junz, Helen (IMF Working Papers; Working Paper ;, 1991)
The sheer size of mandated trade among members of the Council for Mutual Economic Assistance (CMEA), and its composition and quality, means that its reorientation toward other markets entails a whole complex of structural adjustment policies. To be successful, policy reform must be comprehensive, with clarity of purpose and predictability of action. Nevertheless, while gradualism should not be used as an excuse for delay, reforms must be harmonized with the timetable of requisite institutional change. In any case, reform must be accompanied by trade liberalization to help break down domestic monopolies and to gain the efficiencies from division of labor.